228 Factors associated with lymphedema after treatment for uterine cervical neoplasms: a systematic review. (18th September 2019) - Bona, A; Bergmann, A; Boechat de Moura Carvalho, R; Rodrigues Ferreira, K
Abstract : Objectives: Realize a systematic literature review of studies that identified factors associated with lymphedema after treatment for uterine cervical neoplasms. Methods: A systematic review of the literature was performed according to the PRISMA guidelines. Eligible studies were identified through the databases Medline (via PubMed), LILACS, Scopus and Web of Science. For the search, we used descriptors, keywords and synonyms for: uterine cervical neoplasms, lymphedema and outcomes of interest (incidence, prevalence, frequency, occurrence, morbidity, risk factors and prognosis). We included cross-sectional, retrospective or prospective cohort studies, or case-control studies, published in the English, Portuguese or Spanish languages, with frequency data and risk factors for lymphedema after uterine cervical neoplasms treatment. Results: Fifteen studies were included in the review. The risk factors for lymphedema included adjuvant radiotherapy, removal of circumflex iliac lymph nodes, retroperitoneal closure, open surgical procedure, cellulitis, post-surgery lymphocytes, BMI ≥ 25 kg/m², pelvic and para-aortic lymphadenectomy. Conclusions: The different delineations and methodologies employed by the authors make it difficult to compare them and may interfere with the frequency and risk factors associated with lymphedema. There is no consensus on the best method used in the diagnosis of lymphedema and the risk factors are mainly associated with cancer treatment and obesity.